2010
DOI: 10.1038/nature09389
|View full text |Cite
|
Sign up to set email alerts
|

Early warning signals of extinction in deteriorating environments

Abstract: During the decline to extinction, animal populations may present dynamical phenomena not exhibited by robust populations. Some of these phenomena, such as the scaling of demographic variance, are related to small size whereas others result from density-dependent nonlinearities. Although understanding the causes of population extinction has been a central problem in theoretical biology for decades, the ability to anticipate extinction has remained elusive. Here we argue that the causes of a population's decline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
538
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 497 publications
(548 citation statements)
references
References 29 publications
8
538
0
2
Order By: Relevance
“…Populations approaching certain kinds of thresholds have been shown to exhibit generic early warning signals-leading indicators-prior to a transition, a function of a population's diminishing ability to return to its prior state after environmental perturbation, known as critical slowing down (Contamin and Ellison 2009;Drake and Griffen 2010a;Carpenter et al 2011;Dakos et al 2011Dakos et al , 2012b. Such early warning signals include an increase in the standard deviation of a population's size, a decrease in the return rate of a population to its mean after a perturbation, and an increase in the autocorrelation of a population's demographic fluctuations (Dakos et al 2012a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Populations approaching certain kinds of thresholds have been shown to exhibit generic early warning signals-leading indicators-prior to a transition, a function of a population's diminishing ability to return to its prior state after environmental perturbation, known as critical slowing down (Contamin and Ellison 2009;Drake and Griffen 2010a;Carpenter et al 2011;Dakos et al 2011Dakos et al , 2012b. Such early warning signals include an increase in the standard deviation of a population's size, a decrease in the return rate of a population to its mean after a perturbation, and an increase in the autocorrelation of a population's demographic fluctuations (Dakos et al 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…Drake and Griffen (2010a) used a long-term experiment (approximately 60 generations; Ebert 2005) in small-scale aquatic microcosms to show that leading indicators of population collapse could be identified several generations before populations became extinct. Field tests of such signals have been provided by, among others, Carpenter et al (2011), whose whole-lake manipulation demonstrated that statistical signals of a regime shift were detectable more than a year before the shift occurred.…”
Section: Introductionmentioning
confidence: 99%
“…Terrestrial ecosystems respond non-linearly to climate change with multiple factors over long periods (Scheffer et al 2009;Dillon et al 2010;Doak and Morris 2010;Drake and Griffen 2010;Sun et al 2010), and can have tipping points or critical boundaries at which a sudden shift to a contrasting dynamic regime might occur (Rockström et al 2009;Scheffer et al 2009;Dillon et al 2010;Doak and Morris 2010;Drake and Griffen 2010). Significantly, more C is stored in the world's soils than in the above-ground biomass and atmosphere (Davidson and Janssens 2006;Fontaine et al 2007;Gruber and Galloway 2008;Heimann and Reichstein 2008;Piao et al 2009).…”
Section: Soil Carbon and Nutrient Dynamicsmentioning
confidence: 99%
“…One well-known indicator of an approaching bifurcation is critical slowing down, where a system responds sluggishly to external perturbations [1]. This phenomenon has been observed in biological systems as an early warning sign of extinction in species [2]. It has also been used to forecast climate shifts [3,4] and to predict phase transitions in statistical mechanics [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The equilibrium paths for this system are given by 2) and hence for a given control parameter λ we obtain corresponding equilibria,…”
Section: Introductionmentioning
confidence: 99%